Teaching Immunology as a Liberal Art - Chatterjea, Devavani (Frontiers in Immunology, 2020)
A complex, rapidly evolving biomedical field that is of critical relevance to human health and well-being, immunology provides important and substantive opportunities to practice and teach the central tenets of a liberal arts curriculum.